Symptoms, Signs, and EEG Changes During Reflex Syncope - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs)
Investigators at Leiden University Medical Centre, The Netherlands, studied the symptoms, video data of signs, and EEG changes during tilt-induced vasovagal syncope in 69 subjects, age range 12-84 years (mean 46 years).